Targeting thrombomodulin to circulating red blood cells augments its protective effects in models of endotoxemia and ischemia‐reperfusion injury. Issue 2 (11th November 2016) - Carnemolla, Ronald; Villa, Carlos H.; Greineder, Colin F.; Zaitsev, Sergei; Patel, Kruti R.; Kowalska, M. Anna; Atochin, Dmitriy N.; Cines, Douglas B.; Siegel, Don L.; Esmon, Charles T.; Muzykantov, Vladimir R.
ABSTRACT: Endothelial thrombomodulin (TM) regulates coagulation and inflammation via several mechanisms, including production of activated protein C (APC). Recombinant APC and soluble fragments of TM (sTM) have been tested in settings associated with insufficiency of the endogenous TM/APC pathway, such as sepsis. We previously designed a fusion protein of TM [single‐chain variable fragment antibody (scFv)/TM] targeted to red blood cells (RBCs) to improve pharmacokinetics and antithrombotic effects without increasing bleeding. Here, scFv/ TM was studied in mouse models of systemic inflammation and ischemia‐reperfusion injury. Injected concomitantly with or before endotoxin, scFv/TM provided more potent protection against liver injury and release of pathological mediators than sTM, showing similar efficacy at up to 50‐fold lower doses. scFv/TM provided protection when injected after endotoxin, whereas sTM did not, and augmented APC production by thrombin ~50‐fold more than sTM. However, scFv/TM injected after endotoxin did not reduce thrombin/antithrombin complexes; nor did antibodies that block APC anticoagulant activity suppress the prophylactic anti‐inflammatory effect of scFv/TM. Therefore, similar to endogenous TM, RBC‐anchored scFv/TM activates several protective pathways. Finally, scFv/TM was more effective at reducing cerebral infarct volume and alleviated neurological deficits than sTM after cerebral ischemia/reperfusion injury. These results indicate that RBC‐targeted scFv/TM exerts multifaceted cytoprotective effects and may find utility in systemic and focal inflammatory and ischemic disorders.—Carnemolla, R., Villa, C.H., Greineder, C. F., Zaitseva, S., Patel, K.R., Kowalska, M.A., Atochin, D. N., Cines, D.B., Siegel, D.L., Esmon, C. T., Muzykantov, V. R. Targetingthrombomodulin to circulatingred blood cells augments its protective effects in models of endotoxemia and ischemia‐reperfusion injury FASEB J. 31, 761–770 (2017). http://www.fasebj.org